Contrasting functional responses of non-native invasive species along a tropical elevation gradient - Gillerot, Loïc; Negreiros, Daniel; Barbosa, Newton P. U.; Silveira, Fernando A.O.; Paula, Luiza F. A. de (Acta Botânica Brasílica, 2021)
ABSTRACT One hypothesized invasion strategy (“try-harder”) predicts that invaders exhibit functional traits that are better adjusted to the environment than native species. Alternatively, the “join-the-locals” hypothesis predicts trait convergence between invasive and native species due to environmental filtering with increasing resource limitation. We hypothesized that invasions strategies shift from “try-harder” to “join-the-locals” with increasing elevation. We used an elevational gradient to detect possible trait convergences between alien invaders and native plant species in Asteraceae, Fabaceae and Poaceae. We found a significant trait convergence with elevation only in Asteraceae, suggesting a species-specific pattern, but also an important phenotypic variability of the alien invader. This supports the idea that the more resource-limited the environment, the more it filters out traits substantially diverging from the locally-adapted native community, thereby entailing a shift from “try-harder” to “join-the-locals” strategies. The invasive grass was also more acquisitive but did not exhibit any relation to the native community, supporting the “try-harder” hypothesis. The size of the invasive Fabaceae species decreased with elevation, mirroring the native Fabaceae species, but not the overall native community. Including more replicates and a thorough quantification of environmental conditions, offers a promising avenue for improving the understanding the seemingly idiosyncrasies of invasion pathways.